Reduction of bird pest in electrical power substations using sonic devices - Al-Sweedy, Ali Faik Tawfiq (2010)
Birds such as crows, starling flock, feral pigeon and house sparrows are the major problem that cause damage particularly in switchracks, transformers, capacitors and transmission towers that apply to electrical stations and substations. It makes an ideal place for birds to protect themselves and enjoy their food away from peril. Fortunately, modern technology offers electronic bird repeller device such as sonic and ultrasonic and many other preventive measures that can be used to decrease outages due to birds’ intrusion with the electrical stations and substations. Identifying and implementing preventive measures can greatly decrease customer interruptions; therefore, improve customer satisfaction and utility revenues. This thesis presents the method on how to decrease the birds’ intrusion and discuses the utility application of some devices available in the industry that has produced positive results. This study discusses the birds’ intrusion and its damages cause at the substations and electric transmission lines (distribution system). It also analyzes the TNB (Tenaga Nasional Berhad) System Faults Data during the year 1993 to 1999, where most of the faults were attributed to unknown causes, which is found to be mostly due to birds. These electrical faults were mostly the results of short circuits on air isolated medium voltage bus bar system, which in this thesis referred to as “flashover”.